Iowa RBA, February 3, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Iowa RBA update for February 3, 1997. Highlights of the update include the continued presence of an immature Pinyon Jay as well as sightings of Prairie Falcons, an immature Snowy Owl, four Long-eared Owls, and Long-tailed Ducks. Also included are handwritten notes for the next week's update with sightings of Great Gray Owls and Snowy Owls. Epson - sheet feed/flatbed